The impact of silicon brick polishing on thin (120 μm) silicon wafer sawing yields and fracture strengths in diamond-wire sawing. (January 2020) - Sekhar, Halubai; Fukuda, Tetsuo; Tanahashi, Katsuto; Takato, Hidetaka
Abstract: The present study recommends sawing thin (120 μm) silicon (Si) wafers using thin (120 μm) diamond wire with higher throughputs and sawing yields (>96%). In a multi-wire saw, an improved type of diamond wire (100 d/M6-12) is employed to saw ground (g) and mirror-polished (p) Si bricks into thin (120 μm) Si wafers. Improvements in both diamond wire and Si brick surface allow us to saw thin (120 μm) Si wafers with higher fracture strengths and sawing yields of over 96%. The wafers sawn from g and p Si bricks are labeled as g- Si wafers and p- Si wafers. Depending on wire wear position, sawn wafers are labeled as fresh-wire and worn-wire sides. In a three-line bending test, mechanical loads were applied perpendicular to the wire saw marks on the middle of each wafer to measure its fracture strength. Two fundamental differences are observed in the fracture strengths of g- and p- Si wafers. The g- Si wafers fractured at lower strengths compared with the p- Si wafers. Both g- and p- Si wafers from the fresh-wire side fractured at lower strengths compared with worn-wire-side wafers. To address the fracture strength difference, edge chipping and fractographic studies were carried out. The wafer edges were observed at wire entrance and wire exit sides in the Si brick. At the wire exit side, the wafer surface contains a large number of pits followed by longer chipping lengths and widths compared with the wire entrance side. The fractographic studies were performed on fractured samples collected from the middle of the wafer by observing its cross-sections. The wafers fractured at low-strength samples follow mirror mechanisms, and the wafers fractured at intermediate- and higher-strength samples follow any one of mirror–mist, mist, hackle, branching or a mixture of these mechanisms. Graphical abstract: Image 1 Highlights: In diamond multi-wire saw, ground (g) and mirror-polished (p) silicon (Si) bricks are sawn into thin (120 μm) Si wafers using thin (120 μm) diamond wire. The wafer sawing yield for ground (g) Si brick is over 90%, and for mirror-polished (p) Si brick is over 96%. As sawn wafers have higher fracture strengths, we recommend that the photovoltaic industry adopt thin Si wafer-based solar cells in processing in lines in the future.